A sub fertility problem in dairy heifers. Issue 4 (23rd July 2013) - Crawshaw, William Mark
<x xml:space="preserve">Abstract</x> A subfertility problem in a group of 23 dairy heifers was investigated. The diagnosis was bovine venereal campylobacteriosis due to Campylobacter fetus subspecies venerealis biovar intermedius. The clinical features of the case, the investigation procedure (including a simple cost:benefit analysis) and the control method advised are presented. In connection with the case reported, bovine venereal campylobacteriosis is briefly reviewed and the pathological significance of the different subspecies and biovars of Campylobacter fetus is briefly discussed.